2022
DOI: 10.3389/fimmu.2022.966457
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational changes in Phialophora verrucosa via lysine lactylation during prolonged presence in a patient with a CARD9-related immune disorder

Abstract: CARD9-related inherited immune disorders are a major risk factor for chronic disseminated fungal infection. In addition to pathogens of Candida and dermatophytes, the environmental opportunists of the black yeast-like fungi are relatively frequent in this patient cohort. Particularly the genus Phialophora is overrepresented. We investigated two isolates of a strain of P. verrucosa residing in a CARD9 patient, sampled with a period of ten years apart. Genomes, melanization and antifungal susceptibility of proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…A subcellular localization analysis of the 333 lactylated proteins was conducted by using UniProt database notes. As shown in Figure 3A, most of the lactylated proteins in human lungs were distributed in the cytoplasm (29.8%) and nucleus (29.1%), which is the same as the three subcellular localizations with the most lactylated proteins in human gastric cancer cells and other cell types [14–19]. In addition, our analysis revealed that secreted proteins, proteins associated with chromosomes, proteins in the extracellular space and at other locations were lactylated, demonstrating that the lactylation profile of human lungs shows diverse subcellular distributions (Figure 3A).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…A subcellular localization analysis of the 333 lactylated proteins was conducted by using UniProt database notes. As shown in Figure 3A, most of the lactylated proteins in human lungs were distributed in the cytoplasm (29.8%) and nucleus (29.1%), which is the same as the three subcellular localizations with the most lactylated proteins in human gastric cancer cells and other cell types [14–19]. In addition, our analysis revealed that secreted proteins, proteins associated with chromosomes, proteins in the extracellular space and at other locations were lactylated, demonstrating that the lactylation profile of human lungs shows diverse subcellular distributions (Figure 3A).…”
Section: Resultssupporting
confidence: 66%
“…However, it is interesting that the proline (P) residue was found to be enriched in the second position upstream of the Kla site in AGS human gastric cancer cells [11], while in our motifs, it was enriched in the third position downstream of the Kla site. We did not find any same enriched residues in the motifs of other species [15–19], which suggested that lactylated proteins exhibit a specific preference for substrates in different human tissue or cell lines, and the differences among species were great.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The skin microbiome consists of viruses, and bacterial and eukaryotic communities, most of which are natural colonisers while others are ephemeral opportunists or are pathogens potentially involved in cutaneous infections 48,60 . Due to its high exposure to the surroundings, the microbial community of the skin surface constantly loses and acquires microbes 57 . Among eukaryotes, Malassezia is the most frequent coloniser, 50,51,57,59 while dermatophytes are the most common pathogenic fungi in the skin microbiome 48 .…”
Section: Discussionmentioning
confidence: 99%
“…48,60 Due to its high exposure to the surroundings, the microbial community of the skin surface constantly loses and acquires microbes. 57 Among eukaryotes, Malassezia is the most frequent coloniser, 50,51,57,59 while dermatophytes are the most common pathogenic fungi in the skin microbiome. 48 However, some groups have remained unexplored by conventional culture-based methods.…”
Section: Discussionmentioning
confidence: 99%